2016
DOI: 10.1186/s13613-016-0175-z
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence imaging of ATP in neutrophils from patients with sepsis using organelle-localizable fluorescent chemosensors

Abstract: BackgroundThe activation of polymorphonuclear neutrophils (PMNs) plays an important role in sepsis. Previously, we showed that ATP release and feedback via ATP receptors are essential for PMN activation; however, the dynamics remain poorly understood. Two new fluorescent chemosensors, PMAP-1 and MitoAP-1, were developed to detect ATP in the plasma membrane and mitochondria of living cells, respectively. In this study, we aimed to evaluate ATP localization using these chemosensors in PMNs of sepsis patients.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
(46 reference statements)
0
5
0
Order By: Relevance
“…As noted earlier, ATP is present in PMN cells [17][18][19]. ATP is a damage-associated molecular pattern (DAMP) molecule, and is associated with PMN chemoattraction, phagocytosis and apoptosis.…”
Section: Plos Onementioning
confidence: 81%
“…As noted earlier, ATP is present in PMN cells [17][18][19]. ATP is a damage-associated molecular pattern (DAMP) molecule, and is associated with PMN chemoattraction, phagocytosis and apoptosis.…”
Section: Plos Onementioning
confidence: 81%
“…A higher plasma level of adenosine 5′-triphosphate (ATP) is reported in sepsis patients and in animal models of sepsis181183 (Figure 3B). Furthermore, higher intracellular ATP is also observed in neutrophils isolated from sepsis patients 184. Further study in this direction has indicated that higher levels of systemic ATP molecules cause an impairment in neutrophil chemotaxis and host defense 185.…”
Section: Inflammasomes In the Immunopathogenesis Of Sepsismentioning
confidence: 97%
“…ATP breakdown by apyrase was verified in HBSS as well as in LB medium using a luciferase‐based ATP bioluminescence assay kit (Thermo Fisher Scientific). The cell‐surface targeting fluorescent ATP probe 2‐2Zn (kind gift from Dr. Itaru Hamachi, Kyoto University, Kyoto, Japan) and flow cytometry were used for real‐time monitoring of ATP release from individual cells . PMNs were suspended in HBSS containing 1% heparinized human plasma and stained with 2‐2Zn (500 nM) for 5 min.…”
Section: Methodsmentioning
confidence: 99%